Surabaya City Workers, Why Choose an Accountant Career? financial rewards, professional recognition (International Journal of Scientific Research and Management (IJSRM), 2020)
Careers are important for the lives of everyone, especially those of productive age. When someone chooses a career, it is an important matter in the life they lead. Because when someone chooses a career he also chooses to take real steps in fulfilling his life goals. Same with workers who determine their careers. They choose a career according to their abilities, interests and needs. Different abilities, interests and needs of a person. This study uses survey methods with quantitative data to find out why choosing an accountant’s career. The population of this study is workers who are in the city of Surabaya, this is based on the objectives and objects of research conducted by researchers. While the sample of this research is workers who take accounting courses in the city of Surabaya. In this study the results of the analysis of the factors formed by 3 variables used as factors in the selection of accountants’ careers are financial rewards, professional recognition and social values. The factor that shows the dominant value in choosing an accountant’s career is financial rewards.